The Regulation of the Small Heat Shock Protein B8 in Misfolding Protein Diseases Causing Motoneuronal and Muscle Cell Death - Cristofani, Riccardo; Rusmini, Paola; Galbiati, Mariarita; Cicardi, Maria Elena; Ferrari, Veronica; Tedesco, Barbara; Casarotto, Elena; Chierichetti, Marta; Messi, Elio; Piccolella, Margherita; Carra, Serena; Crippa, Valeria; et al. (Frontiers in Neuroscience, 2019)
Misfolding protein diseases are a wide class of disorders in which the aberrantly folded protein aggregate accumulating in affected cells. In the brain and in the skeletal muscle, misfolded protein accumulation induces a variety of cell dysfunctions that frequently lead to cell death. In motoneuron diseases (MNDs), misfolded proteins accumulate primarily in motoneurons, glial cells and/or skeletal muscle cells, altering motor function. The deleterious effects of misfolded proteins can be counteracted by the activity of the protein quality control (PQC) system, composed of chaperone proteins and degradative systems. Here, we focus on the PQC system components: heat shock protein family B (small) member 8 (HSPB8), a chaperone induced by harmful stressful events, including proteotoxicity. In motoneuron and muscle cells, misfolded proteins activate HSPB8 transcription and enhance HSPB8 levels, which contributes to prevent aggregate formation and their harmful effects. HSPB8 acts not only as chaperone, but also facilitates the autophagy process, to enable the efficient clearance of the misfolded proteins. HSPB8 acts as a dimer bound to the HSP70 co-chaperone BAG3, a scaffold protein that is also capable of binding to HSP70 (associated with the E3-ligase CHIP) and dynein. When this complex is formed, it is transported by dynein to the microtubule organization center (MTOC), where aggresomes are formed. Here, misfolded proteins are engulfed into nascent autophagosomes to be degraded via the chaperone-assisted selective autophagy (CASA). When CASA is insufficient or impaired, HSP70 and CHIP, associate with an alternative co-chaperone, BAG1, which routes misfolded proteins to the proteasome for degradation. The finely-tuned equilibrium between proteasome and CASA activity is thought to be crucial for maintaining the functional cell homeostasis during proteotoxic stresses, which in turn is essential for cell survival. This fine equilibrium seems to be altered in MNDs, like Amyotrophic lateral sclerosis (ALS) and spinal and bulbar muscular atrophy (SBMA), contributing to the onset and the progression of disease. Here, we will review how misfolded proteins may affect the PQC system, and how the proper activity of this system can be restored by boosting or regulating HSPB8 activity, with the aim to ameliorate disease progression in these two fatal MNDs.